2022
DOI: 10.1002/bit.28173
|View full text |Cite
|
Sign up to set email alerts
|

On‐line untargeted metabolomics monitoring of an Escherichia coli succinate fermentation process

Abstract: The real-time monitoring of metabolites (RTMet) is instrumental for the industrial production of biobased fermentation products. This study shows the first application of untargeted on-line metabolomics for the monitoring of undiluted fermentation broth samples taken automatically from a 5 L bioreactor every 5 min via flow injection mass spectrometry. The travel time from the bioreactor to the mass spectrometer was 30 s. Using mass spectrometry allows, on the one hand, the direct monitoring of targeted key pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The bioconversion of succinic acid can be carried out using various strains of microorganisms, and the possibility of using various carbon sources as a fermentation medium (including waste sources) makes the process in line with the principles of sustainable development. In the upstream stage, fermentation broth is obtained and the required process conditions and the appropriate pH generate succinate as a product. , As a result, downstream processing requires not only purification from byproducts, biomass, and unreacted medium but also conversion of the carboxylate to the free acid form. Most of the methods possible to separate succinic acid and presented in Figure require preliminary treatment and acidification of the solution and do not provide direct separation of the carboxylate (sodium succinate).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioconversion of succinic acid can be carried out using various strains of microorganisms, and the possibility of using various carbon sources as a fermentation medium (including waste sources) makes the process in line with the principles of sustainable development. In the upstream stage, fermentation broth is obtained and the required process conditions and the appropriate pH generate succinate as a product. , As a result, downstream processing requires not only purification from byproducts, biomass, and unreacted medium but also conversion of the carboxylate to the free acid form. Most of the methods possible to separate succinic acid and presented in Figure require preliminary treatment and acidification of the solution and do not provide direct separation of the carboxylate (sodium succinate).…”
Section: Resultsmentioning
confidence: 99%
“…In the upstream stage, fermentation broth is obtained and the required process conditions and the appropriate pH generate succinate as a product. 45,46 As a result, downstream processing requires not only purification from byproducts, biomass, and unreacted medium but also conversion of the carboxylate to the free acid form. Most of the methods possible to separate succinic acid and presented in Figure 14 require preliminary treatment and acidification of the solution and do not provide direct separation of the carboxylate (sodium succinate).…”
Section: ■ Resultsmentioning
confidence: 99%
“…On-line metabolomics was conducted by connecting the fermenter to a TSQ Quantiva triple quadrupole (Thermo Scientific) mass spectrometer with the fluidics system previously described by Cortada-Garcia et al (2022) but the fermentation broth samples were subtracted from the bioreactor using a biomass filtration probe (TRACE Analytics GmbH) equipped with a polypropylene membrane.…”
Section: On-line Metabolomicsmentioning
confidence: 99%
“…However, this approach is limited to volatile molecules, whereas fermentation monitoring with MS directly from the liquid broth is a much less developed approach. The authors recently demonstrated the use of untargeted on‐line metabolomics (RTMet) directly sampling from the liquid phase as a bioprocess monitoring tool with an Escherichia coli fermentation process of succinate production (Cortada‐Garcia et al, 2022 ). In the study, the authors used a high‐resolution Orbitrap mass spectrometer, which allows the detection of metabolites with a mass tolerance of 5 ppm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation